MINERALISASI ENDAPAN SINABAR DAERAH BUKIT TEMBAGA KECAMATAN HUAMUAL, KABUPATEN SERAM BAGIAN BARAT, MALUKU: MINERALIZATION OF CINNABAR DEPOSIT AT TEMBAGA HILL, HUAMUAL DISTRICT, WESTERN SERAM REGENCY, MALUKU - Herfien Samalehu; Arifudin Idrus; Nugroho Imam Setiawan (Buletin Sumber Daya Geologi, 2022)
Iha – Luhu is located in the western part of Seram Island, Maluku which is placed at an elevation of 9 up to 341 meters above sea level and occupies Taunusa Metamorphic Complex. This study aims to study geological control, mineralization characteristics and ore geochemistry of cinnabar deposit in Iha - Luhu. Research method applies a literature review, fieldwork for sampling, geological mapping, alteration & mineralization and laboratory analysis including polished section, ore geochemistry (FA/AAS and ICP-AES, XRF) and elemental mapping (Micro-XRF). The results showed that characteristics of cinnabar deposits in Iha – Luhu were formed in two type of veins (fracture-related mineralization) and disseminated in metapelites and quartz-muscovite phyllite hostrocks and controlled by NNW-SE and NE- SW trending faults. Mineralization consists of cinnabar (±metacinnabar), arsenopyrite, stibnite, sphalerite, hematite, minor pyrite±pyrrhotite with gangue minerals consisting of quartz, illite, smectite and kaolinite. Cinnabar ore contains an abundance of Zn, Sb, Fe, As, indicating presence of precious metal (gold) and mercury (Hg) content reaching 72.4%.